2021
DOI: 10.3390/cancers13194955
|View full text |Cite
|
Sign up to set email alerts
|

TIMP1 and TIMP2 Downregulate TGFβ Induced Decidual-like Phenotype in Natural Killer Cells

Abstract: Natural Killer (NK) cells have been found to be anergic, exhausted and pro-angiogenic in cancers. NK cell from healthy donors, exposed to TGFβ, acquire the CD56brightCD9+CD49a+ decidual-like-phenotype, together with decreased levels of NKG2D activation marker, increased levels of TIM-3 exhaustion marker, similar to cancer-associated NK cells. Tissue inhibitors of metalloproteases (TIMPs) exert dual roles in cancer. The role of TIMPs in modulating immune cells is a very novel concept, and the present is the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Pro-angiogenic decidual-like NK (dNK-like) cells, characterized by the CD56 bright CD16 -VEGF high CXCL8 + IFN low subset, has been found in tumor infiltrating and circulating NK cells in NSCLC [153], pleural effusion of patients with metastatic cancers [154] and CRC patients [155]. These dNK-like cells have been found to be induced by TGFβ, as also confirmed by experimental in vitro models of TGFβ polarized cytolytic NK cells [149,153,154,156,157].…”
Section: Nk Cellsmentioning
confidence: 66%
“…Pro-angiogenic decidual-like NK (dNK-like) cells, characterized by the CD56 bright CD16 -VEGF high CXCL8 + IFN low subset, has been found in tumor infiltrating and circulating NK cells in NSCLC [153], pleural effusion of patients with metastatic cancers [154] and CRC patients [155]. These dNK-like cells have been found to be induced by TGFβ, as also confirmed by experimental in vitro models of TGFβ polarized cytolytic NK cells [149,153,154,156,157].…”
Section: Nk Cellsmentioning
confidence: 66%
“…MYL12A was proved to be involved in DNA damage repair and p53-driven apoptosis [ 28 ]. TIMP1 is member of natural inhibitors of the matrix metalloproteinases, which has the effect of controlling the polarization of Natural Killer cells induced by the tumor-related cytokine TGFβ [ 29 ]. CCDC109B was involved in the activation of cell death pathway.…”
Section: Discussionmentioning
confidence: 99%
“…CCDC109B was involved in the activation of cell death pathway. Xu et al showed that it plays an important role in mediating the migration and invasion of glioma cells induced by HIF1α [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…TIMP1, CCL2 and SERPINE1 are the core nodes in the PPI network of 25 genes. The main function of metallopeptidase inhibitor 1 (TIMP1) is to inhibit the activity of metalloproteinases(MMP), which in turn exerts its pro-cancer effect [27]. TIMP1 is highly expressed in gliomas, it correlates with immune cell markers and m6A [28].…”
Section: Discussionmentioning
confidence: 99%